2020
DOI: 10.47391/jpma.414
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D levels with preeclampsia

Abstract: Abstract Objectives: This study was aimed to assess maternal vitamin D status during pregnancy and  determine the association between maternal 25(OH) D levels with risk of preeclampsia (PE). Methods: A cross-sectional study was conducted with 172 pregnant women recruited from JPMC between January and December 2017 who were divided as normotensive (n=80) and pre-eclamptic (n=92) groups. Blood pressure was recorded at 20 and 32 weeks of gestation. Five ml of blood sample was collected at 20 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Despite these observations, the human clinical research reveals inconsistent results in this field. Shahid et al observed a significantly lower VD level in the PE group compared to healthy normotensive women (p < 0.001), as well as a negative correlation of VD level with systolic (p < 0.001) and diastolic blood pressure (p < 0.001) [54]. Zeng et al reported that low VD level could be a risk factor for early-and late-onset PE occurrence [55].…”
Section: Vdr Protein Level In Placentasmentioning
confidence: 98%
“…Despite these observations, the human clinical research reveals inconsistent results in this field. Shahid et al observed a significantly lower VD level in the PE group compared to healthy normotensive women (p < 0.001), as well as a negative correlation of VD level with systolic (p < 0.001) and diastolic blood pressure (p < 0.001) [54]. Zeng et al reported that low VD level could be a risk factor for early-and late-onset PE occurrence [55].…”
Section: Vdr Protein Level In Placentasmentioning
confidence: 98%
“…According to several studies, low concentrations of 25(OH)D and 1,25(OH)2D correlate with high systolic and diastolic blood pressure (BP) during pregnancy [58][59][60][61][62][63] and only a few papers have demonstrated opposite results [64]. Because vitamin D is an approved supplement during pregnancy, Nassar, Seham Zakaria, and Noha Mohamed Badae tested the hypothesis of lowering systolic BP by vitamin D supplementation and found that its administration reduced systolic BP, proteinuria [65].…”
Section: Effect Of Vitamin D Concentrations On Hypertensive Disorders...mentioning
confidence: 99%
“…Thus, the level of 25(OH)D may be one of the causes of arterial hypertension in preeclampsia. According to several studies, low concentrations of 25(OH)D and 1,25(OH)2D correlate with high systolic and diastolic BP during pregnancy [ 59 , 60 , 61 , 62 , 63 , 64 ], and only a few papers have demonstrated the opposite results [ 65 ]. Because 25(OH)D is an approved supplement during pregnancy, Nassar, Seham Zakaria, and Noha Mohamed Badae tested the hypothesis of lowering systolic BP by 25(OH)D supplementation and found that its administration reduced systolic BP and proteinuria [ 66 ].…”
Section: Impact Of 25(oh)d Concentrations On the Development Of Arter...mentioning
confidence: 99%